Relationship between vocabulary learning strategies, perceptual learning styles and levels of vocabulary knowledge among Iranian EFL learners - Yazdi, Mahdi (2013)
This study tries to investigate the vocabulary learning strategies, learning styles and vocabulary level of Iranian EFL learners and any potential relation and contribution between these variables. The research design of this study is primarily quantitative although qualitative data collection was applied to address the last research question “What are the tendencies of Iranian EFL students with high and low vocabulary knowledge in applying vocabulary learning strategies?” 238 participants both male and female were selected from Semnan universities according to random cluster sampling. Schmitt’s vocabulary learning strategies questionnaire (VLSQ), Ried’s perceptual learning styles preferences questionnaires (PLSPQ), Nation’s vocabulary level test (VLT) and Kafipour’s approach for journal writing protocol were used to collect data. The results showed that Iranian junior EFL students can be classified as medium strategy users with overall strategy mean score of 2.99 out of 5. It indicated that the participants of the current study need more training on vocabulary learning strategies to become more familiar with all types of vocabulary learning strategies. The study also indicated that memory strategy was found as the most frequently used strategy with mean score of 3.03 and cognitive strategy as the least frequently used with mean score of 2.95 out of 5. The analysis of perceptual learning style preferences showed that the learners mostly preferred the individual learning style (mean score=32.64 out of 50) while auditory learning style was the least preferred learning style (mean score=27.69 out of 50); however, none of the learning styles were found as a major preference of the learners. The descriptive statistics showed that the vocabulary knowledge level of students is very good at 2000 as they knew 905 out of 1000 words available in this level and 3000 levels as they knew 850 out of 1000 words available in this level and good at AWL level as they knew 407 out of 570 words available in this level but low at 5000 word level as they knew 571 out of 1000 words available in this level and very low at 10000 word level as they knew 195 out of 1000 words available in this level. The results also indicated that there was significant relationship between vocabulary learning strategies and vocabulary knowledge levels of the students (r= 0.371). There was high correlation between memory strategy and 3000 word level (r=0.36) and low correlation between social strategy and 3000 word level (r=0.12) as well. The multiple regression was run to determine the amount of contribution of vocabulary learning strategies to vocabulary knowledge level. The elicited results were also the same as correlation results. Memory (β=0.37, T=6.13, Sig. T=0.00) and social strategies (β=0.20, T=3.97, Sig. T=0.00) made the highest and lowest contribution to vocabulary knowledge levels respectively. At the end, two high and low proficient groups who were selected out of vocabulary level test (Nation, 2002) were qualitatively scrutinized to find out type of vocabulary learning strategies they applied. The finding revealed that the more vocabulary pool learners have the more variety of vocabulary learning strategies they will use. For the same reason, high vocabulary knowledge respondents tended to use mixed vocabulary learning strategies in comparison with low vocabulary knowledge learners.